2021
DOI: 10.1002/cbic.202100291
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Assays to Explore Viral mRNA Capping Machinery

Abstract: In eukaryotes, mRNA is modified by the addition of the 7‐methylguanosine (m 7 G) 5′ cap to protect mRNA from premature degradation, thereby enhancing translation and enabling differentiation between self (endogenous) and non‐self RNAs (e. g., viral ones). Viruses often develop their own mRNA capping pathways to augment the expression of their proteins and escape host innate immune response. Insights into this capping system may provide new ideas for therapeutic interventions and facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 176 publications
0
16
0
Order By: Relevance
“…1 H NMR (500 MHz, DMSO-d 6 ): δ 8.74 (t, J = 6.1 Hz, 1H), 8.45 (dd, J = 7.0, 2.4 Hz, 1H), 8.27 (s, 1H), 8.17−8.11 (m, 2H), 7.73 (dd, J = 10.9, 8.7 Hz, 1H), 7.35 (br s, 2H), 5.81 (d, J = 6.2 Hz, 1H), 5.49 (d, J = 6.2 Hz, 1H), 5.29 (d, J = 4.7 Hz, 1H), 4.65 (q, J = 6.0 Hz, 1H), 4.07 (td, J = 5.0, 3.2 Hz, 1H), 3.97 (td, J = 4.9, 3.2 Hz, 1H), 3.26−3.11 (m, 2H). 13 N-{[(2R,5R)-5-(6-amino-9H-purin-9-yl)-3,4-dihydroxyoxolan-2yl]methyl}-4-bromo-3-nitrobenzenesulfonamide (12). Following method E with 41j (94 mg, 0.17 mmol, 1.00 equiv), 12 (54 mg, 62%) was obtained as a beige solid.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (500 MHz, DMSO-d 6 ): δ 8.74 (t, J = 6.1 Hz, 1H), 8.45 (dd, J = 7.0, 2.4 Hz, 1H), 8.27 (s, 1H), 8.17−8.11 (m, 2H), 7.73 (dd, J = 10.9, 8.7 Hz, 1H), 7.35 (br s, 2H), 5.81 (d, J = 6.2 Hz, 1H), 5.49 (d, J = 6.2 Hz, 1H), 5.29 (d, J = 4.7 Hz, 1H), 4.65 (q, J = 6.0 Hz, 1H), 4.07 (td, J = 5.0, 3.2 Hz, 1H), 3.97 (td, J = 4.9, 3.2 Hz, 1H), 3.26−3.11 (m, 2H). 13 N-{[(2R,5R)-5-(6-amino-9H-purin-9-yl)-3,4-dihydroxyoxolan-2yl]methyl}-4-bromo-3-nitrobenzenesulfonamide (12). Following method E with 41j (94 mg, 0.17 mmol, 1.00 equiv), 12 (54 mg, 62%) was obtained as a beige solid.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Curiously, until recently, few inhibitors of the viral MTase nsp14 have been developed, and the lack of selective inhibitors is an exciting challenge not only for new antiviral therapies but also for functional studies of this enzyme. 12 It is noteworthy that nsp14 has an original fold, 13 which is not the canonical Rossmann fold, and that the N 7-MTase domains of CoVs are highly conserved. This particular structural organization and sequence conservation could facilitate the development of specific inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…GO analysis showed that DEGs were primarily enriched in the translational initiation activity, regulation of translation, RNA 7−methylguanosine, etc. Existing studies have modified mRNA by adding an m 7 G 5′ cap to protect mRNA from premature degradation ( Kasprzyk and Jemielity, 2021 ). EGFR plays a crucial role in the METTL1-m7G axis in bladder cancer ( Ying et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As alphaviral mRNA is transcribed, the non-structural protein 1 (nsP1) facilitates the biosynthesis of a 7-methylguanosine nucleotide (m 7 -G), tethered by a triphosphate moiety (ppp, or TP), to the 5′ end of the mRNA strand. This 5′ cap prevents cellular enzyme-driven RNA degradation and aids in host immune response evasion, thereby blunting barriers to viral protein synthesis [ 123 , 124 , 125 ]. The 5′ cap is generated through a series of chemical reactions.…”
Section: Direct Targeting Of Eev Non-structural Proteins (Nsps) With ...mentioning
confidence: 99%
“…The nsP1 mediates the N-methylation of GTP via a methyltransferase [MTase reaction] to generate m 7 -GTP. This is followed by guanylylation of nsP1 to form an nsP1-m 7 -GMP adduct [GT reaction] between viral nsP1 and m 7 -GTP with concomitant extrusion of inorganic pyrophosphate [ 123 , 126 ]. Transfer of the m 7 -GMP moiety to the 5′-diphosphate appendage of the RNA affords the capped strand, m 7 G(5′)ppp(5′)RNA.…”
Section: Direct Targeting Of Eev Non-structural Proteins (Nsps) With ...mentioning
confidence: 99%